Educación Sexual en adolescentes de una institución educativa de un cantón de la provincia de El Oro. - Jumbo Armijos, Selene Esthefania; Ramon MerchÁn, Adriana Elizabeth (My University, 2024)
Adolescence is a critical stage of human development in which knowledge, attitudes, and practices are established that will influence future sexual and reproductive health. This study evaluated the impact of an educational intervention on sexuality among adolescent students at a public educational institution in Pasaje, Ecuador. A quantitative, descriptive, and cross-sectional approach was used with a sample of 216 students aged 13 to 16. A validated questionnaire was applied to assess knowledge, attitudes, and sexual practices before and after the program. The results showed significant improvements in knowledge about sexual anatomy, the menstrual cycle, sexually transmitted infections (STIs), and the correct use of condoms. The percentage of students who understood the risks of unprotected sex increased from 55.6% to 100%, and those who knew how to properly use a condom rose from 32.9% to 100%. A positive shift in attitudes was also observed: the perception of sexuality as an integral dimension increased, and erroneous beliefs were reduced. Additionally, a decrease in risky sexual behaviors and a voluntary delay in sexual initiation were reported. A notable change was seen in sources of information: whereas Internet and peers were predominant before, after the intervention, mothers were more highly valued as educational figures. In conclusion, comprehensive sexuality education, with a gender perspective, culturally adapted and sustained over time, proved to be an effective tool for promoting informed sexual decisions, reducing risks, and fostering adolescent well-being
La adolescencia es una etapa fundamental del desarrollo humano en la que se consolidan los conocimientos, actitudes y prácticas que influyen en la salud sexual y reproductiva futura. Este estudio permitió evaluar el impacto de una intervención educativa sobre sexualidad en estudiantes adolescentes de una institución educativa pública en Pasaje, Ecuador. Se utilizó un enfoque cuantitativo, descriptivo y transversal, con una muestra de 216 estudiantes de entre 13 y 16 años. A través de un cuestionario validado, se midieron conocimientos, actitudes y prácticas sexuales antes y después del programa. Los resultados evidenciaron mejoras significativas en el conocimiento sobre anatomía sexual, ciclo menstrual, infecciones de transmisión sexual (ITS), y uso correcto del preservativo. El porcentaje de estudiantes que comprendía los riesgos del sexo sin protección aumentó del 55,6% al 100%, y quienes sabían utilizar adecuadamente un condón pasaron del 32,9% al 100%. También se observó una transformación positiva en las actitudes: aumentó la percepción de la sexualidad como dimensión integral y se redujeron las creencias erróneas. Además, se reportó una disminución de prácticas sexuales de riesgo y un retraso voluntario en el inicio sexual. Destaca el cambio en las fuentes de información: mientras que antes predominaban Internet y los pares, tras la intervención se revalorizó el rol educativo de las madres. En conclusión, la educación sexual integral, con enfoque de género, culturalmente adaptada y sostenida, demostró ser una herramienta eficaz para promover decisiones sexuales informadas, reducir riesgos y fomentar el bienestar adolescente.
Keywords: ADOLESCENTE; EDUCACION SEXUAL; SERVICIOS DE ENFERMERIA ESCOLAR